2(u-3)=2u+4-2(-6u-3)

Simple and best practice solution for 2(u-3)=2u+4-2(-6u-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(u-3)=2u+4-2(-6u-3) equation:


Simplifying
2(u + -3) = 2u + 4 + -2(-6u + -3)

Reorder the terms:
2(-3 + u) = 2u + 4 + -2(-6u + -3)
(-3 * 2 + u * 2) = 2u + 4 + -2(-6u + -3)
(-6 + 2u) = 2u + 4 + -2(-6u + -3)

Reorder the terms:
-6 + 2u = 2u + 4 + -2(-3 + -6u)
-6 + 2u = 2u + 4 + (-3 * -2 + -6u * -2)
-6 + 2u = 2u + 4 + (6 + 12u)

Reorder the terms:
-6 + 2u = 4 + 6 + 2u + 12u

Combine like terms: 4 + 6 = 10
-6 + 2u = 10 + 2u + 12u

Combine like terms: 2u + 12u = 14u
-6 + 2u = 10 + 14u

Solving
-6 + 2u = 10 + 14u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-14u' to each side of the equation.
-6 + 2u + -14u = 10 + 14u + -14u

Combine like terms: 2u + -14u = -12u
-6 + -12u = 10 + 14u + -14u

Combine like terms: 14u + -14u = 0
-6 + -12u = 10 + 0
-6 + -12u = 10

Add '6' to each side of the equation.
-6 + 6 + -12u = 10 + 6

Combine like terms: -6 + 6 = 0
0 + -12u = 10 + 6
-12u = 10 + 6

Combine like terms: 10 + 6 = 16
-12u = 16

Divide each side by '-12'.
u = -1.333333333

Simplifying
u = -1.333333333

See similar equations:

| x^5-x^4+x-1=0 | | 6x^2-17xy+7y^2=0 | | 3y-1=y^2+1 | | x^3+9x^2-3x-27= | | -3z+4=-z-2 | | -t+(5t-7)=-6 | | a=5b+9c | | (x-2)^2/3=38 | | 4x-36/x=0 | | x^3=9x^2-3x-27 | | 3(16-2)/2= | | 5(2n-2)=(8n+3)+8 | | -3.1(7.5w+7)-6= | | 293+6y= | | 19x-(6x-9)=87 | | 20+5h=25 | | DX+HY= | | 293+6y=500 | | 0.75x+1.5=6x+72 | | 2ln(x-5)=54 | | 7.5(-3.1w-6)+7= | | 7(x+10)=210 | | -6/5y=42 | | 7a=12 | | 10x+4=p | | 25x^2-10=2 | | ax-b=cx-7 | | 2b^2-9b+9= | | 7(x+5)=6(x-6)+x | | 3x-5=-6x+14 | | 3x-5=-6+14 | | 6y+9+9y= |

Equations solver categories